USING AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) MODEL TO MEASURE THE IMPACT OF OIL PRICES ON IRAQ'S INTERNAL DEBT FOR THE PERIOD 2021-2004 - Asst. Prof. Dr. Ibrahim Abdullah Jasim; College of Administration and Economics - Tikrit University (Scholars Digest Publishing, 2024)
The research aims to analyze the changes in oil prices and their effect on Iraq's internal debts for the period (2004-2021) using the Auto Regressive Distributed Lag (ARDL) model. The ARDL model is one of the most prominent models used to analyze the dynamic relations among the economic variables in the short and long terms. The research hypothesis is that there is a direct effect and an inverse relationship between oil prices and internal debt. The research adopts the time series data; applying the stationarity test using the Phillips–Perron test, all the data stabilized after considering the first difference. Consequently, ARDL models were built and estimated for the research variables, as well as conducting determination tests to ensure the models were free of standard problems. The researcher applies the Akaike test to determine the optimal lag length. A set of conclusions was found, and most importantly as follows: An increase in oil prices by one unit leads to a decrease in domestic public debt by a percentage (0.584) at a significant level of (5%).